La Méditerranée comme frontière dans le récit de voyage (riḥla) d’Ibn Ǧubayr - Yann Dejugnat (Mélanges de la Casa de Velázquez, 2008)
The account of a journey(riḥla)by Ibn Ǧubayr is well-known as a source for historians studying the East and the Mediterranean at the time of the Crusades.Whereas hitherto it was used essentially as a factual data base and no attention was paid to the text as such, current research looks at the structure of the account and the narrative devices used, approaching it as a discourse.In adopting this perspective, the article seeks to follow a particular discourse in which the Mediterranean is perceived as a frontier and to identify the modes and challenges of that perception.And indeed, thanks to his «sojourns» on the margins of Islam and thanks to his «account», Ibn Ǧubayr  was a pioneer in identifying the Mediterranean as a frontier of Islam. His writing was also propagandistic in intent; the siting of Islam’s frontier on the Mediterranean allowed the Almohad Caliphate, the leading Muslim maritime power, to assume the role of Islam’s ultimate defender and protector of the Holy Places, the cornerstone of universal power in the Muslim world.